Development of a pharmacy counseling tool for type 2 diabetes mellitus Filipino patients - Leal, Bianca G.
Background : In the community setting, there is a great opportunity for pharmacist's to assists in the management of diabetes mellitus. However, there pharmacist's-based barriers in the provision of patient counseling including lack of time, knowledge, confidence, training, and remuneration (Adepu and Negavi, 2009).Objectives : The study aims to develop and demonstrate the use of a pharmacy counseling tool for type II diabetes mellitus Filipino patients. Methods : A pharmacy counseling tool for type 2 diabetes mellitus Filipino patients was created based on local and international guidelines and manual for diabetes care. The pharmacy counseling tool is composed of a reference manual and two flip charts. Its face, construct and content validity were established by a panel of experts consisting of an internist, a pharmacist and two nurses. Three patients were sampled for the pilot study. Results : All three patients showed an improvement in knowledge, attitude, and practice after counseling (p = 0.1088). Clinical outcomes show that the mean systolic blood pressure of the three patients increased by 6.67 mm Hg. The diastolic blood pressure remained unchanged Random blood glucose had an average decrease of 3.33 mg/dL (p = 0.1573, 1.000 and 1.000). Both the patients and the pharmacist perceived the pharmacy counseling tool useful in meeting the need of patients, and pharmacists. Recommendations : A longer study period and a larger sample size may be employed to detect statistically significant changes in knowledge, attitude, practice, and clinical measures of patients. For the training of the pharmacist, at least one day should be allotted for the review of materials. It may include a lecture on communication to improve the pharmacists skills in asking questions and tailoring the counseling according to the needs of the patients. For a better follow up of patients, the study may also be done in an institutional pharmacy setting.